An indentation in a 33,000-year-old right calcaneus of the ground sloth Lestodon (Xenarthra, Folivora) from Uruguay and its possible human agency - Richard A. Fariña; Elspeth Hayes; Luis A. Lemoine; Richard Fullagar; P. Sebastián Tambusso; Luciano Varela (Swiss Journal of Palaeontology)
Abstract Several sites in the Americas are proposed to have evidence of human occupation before the Last Glacial Maximum (LGM). The timing of human colonisation of the Americas is a matter of debate due to its intrinsic interest, but also because of the implications of that arrival for the extinction of the megafauna. Here, we study a notable indentation in the right calcaneus of a giant extinct ground sloth Lestodon armatus from the Arroyo del Vizcaíno site, Uruguay, dated to ~ 33 cal kyBP. We use a combination of 3D CT-scan modelling, high-resolution silicone casting, and microscopic wear and residue analysis to describe the morphology of the lesion, its associated residues, and the possible mechanisms behind its formation. Considering the indentation’s features, including its shape, depth, and the presence of organic residues, we argue that it could have been created by a penetrating object with a rounded tip, possibly a bone, ivory or hardened wood tip attached to a shaft. This evidence contributes to discussions on the dates of human arrival in South America and the potential interactions with the megafauna.